2018
DOI: 10.1038/s41467-018-06286-y
|View full text |Cite
|
Sign up to set email alerts
|

A distal centriolar protein network controls organelle maturation and asymmetry

Abstract: A long-standing mystery in the centrosome field pertains to the origin of asymmetry within the organelle. The removal of daughter centriole-specific/enriched proteins (DCPs) and acquisition of distal appendages on the future mother centriole are two important steps in the generation of asymmetry. We find that DCPs are recruited sequentially, and their removal is abolished in cells lacking Talpid3 or C2CD3. We show that removal of certain DCPs constitutes another level of control for distal appendage (DA) assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 55 publications
3
78
6
Order By: Relevance
“…4b), which is a known distal appendage marker for the mother centriole, and the distal ends of centrioles are capped by CP110. A similar finding was also noted in a very recent report 23 . Based on our present findings, we conclude that when cells lose CEP120, they experience impairments in the recruitment of C2CD3 and Talpid3, but not CP110, to the distal ends of centrioles.
Figure 4Super-resolution (3D-SIM) microscopic analysis of centriolar distal-end proteins.
…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4b), which is a known distal appendage marker for the mother centriole, and the distal ends of centrioles are capped by CP110. A similar finding was also noted in a very recent report 23 . Based on our present findings, we conclude that when cells lose CEP120, they experience impairments in the recruitment of C2CD3 and Talpid3, but not CP110, to the distal ends of centrioles.
Figure 4Super-resolution (3D-SIM) microscopic analysis of centriolar distal-end proteins.
…”
Section: Resultssupporting
confidence: 91%
“…Talpid3 was previously reported to be essential for ciliary vesicle docking during ciliogenesis 20 . A very recent report showed that Talpid3 is physically associated with C2CD3 at the distal ends of centrioles and such an association is essential for centriole maturation and DA assembly 23 .…”
Section: Introductionmentioning
confidence: 99%
“…DAs comprise the proteins C2CD3 and Cep83 that are essential for the recruitment of additional DAs, such as Cep123/Cep89, SCLT1, LRRC45, Cep164, and FBF1 ( Fig. 1 A ; Tanos et al, 2013 ; Ye et al, 2014 ; Kurtulmus et al, 2018 ; Wang et al, 2018 ). DAs are essential at initial stages of cilia formation in order to establish the interaction between the basal body (a modified M-centriole) and the ciliary membrane compartment ( Schmidt et al, 2012 ; Tanos et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, 16 subtypes have been identified in OFDS, where all appear to represent a classic ciliopathy, with the disease genes coding for ciliary proteins . The OFD1 protein is mainly found within the basal body/centrosome, where it is important for centriole maturation and assembly of subdistal appendages . Mouse Ofd1 is required for formation of primary cilia and determination of left–right asymmetry .…”
Section: Discussionmentioning
confidence: 99%